2004
DOI: 10.1177/0363546503262204
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of a Knee Brace with a Constraint to Knee Extension on Knee Kinematics and Ground Reaction Forces in a Stop-Jump Task

Abstract: The specially designed knee brace may be a useful device in the prevention and rehabilitation of noncontact anterior cruciate ligament injuries in sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 26 publications
(48 reference statements)
5
65
0
1
Order By: Relevance
“…Our results support our first hypothesis that after ACL reconstruction, patients would increase their knee flexion angle at initial foot contact for selected functional activities while wearing the knee extension constraint brace. These results are consistent with those of previous studies for recreational athletes without ACL injuries [27,42].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results support our first hypothesis that after ACL reconstruction, patients would increase their knee flexion angle at initial foot contact for selected functional activities while wearing the knee extension constraint brace. These results are consistent with those of previous studies for recreational athletes without ACL injuries [27,42].…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that after ACL reconstruction, patients decreased their peak posterior ground reaction force during level walking while wearing the knee extension constraint brace. These results are also consistent with those of previous studies for recreational athletes without ACL injuries [27,42]. However, our patients did not show a decrease in the peak posterior ground reaction force during jogging and stair descent while wearing the knee extension constraint brace.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations